Implementasi Extreme Programming (XP) Agile Software Development pada Pengembangan Sistem Informasi KELUARGAKU - Trisnadoli, Anggy (Jurnal Informatika Universitas Pamulang, 2021)
The Pusat Pelayanan Keluarga Sejahtera (PUSYANRA) Lancang Kuning, is a service unit established by the Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) Representative of Riau Province. PUSYANRA has several main tasks as consultants and educates families in Indonesia to become prosperous families. So far, the activities of PUSYANRA Lancang Kuning run randomly and are documented manually, so there are several problems in monitoring activities, displaying activities publicly and compiling annual and monthly reports. One of the things that can be done to optimize these needs is to develop a web-based information system. The information system can be a place to display information as well as a media to educate the public according to the needs of PUSYANRA Lancang Kuning to maximize information and education in implementing PUSYANRA's work program. In addition, regarding reports, activity management and others, web application technology can help administrators to make it easier to carry out their duties. Another problem is the use of this Information System is needed in a fairly short time, because community services continue to run all the time. For the concept of software development with Agile method is a suitable method applied in this case. Based on the development process that has been carried out, this research shows that the Agile Software Development concept can be used properly. As well as the benefits of the Information System can be felt well by all users, so that the "KELUARGAKU" Information System can help PUSYANRA Lancang Kuning in carrying out its work program better.